Transformasi Kelas Digital dan Dampak Implementasi TIK terhadap Literasi Digital Pendidik: Pendekatan Mixed Methods - Arif Rumiyadi; Roza Cyintia Salwa Azhar; Yusuf Nurrahman; Arif Fahrudin; Budi Murtiyasa (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
The gap between the rapid demands of digital transformation in education, which include the adoption of ICT-based learning, LMS, and the integration of Coding and Artificial Intelligence materials, and the reality of implementation challenges in the field. These crucial challenges include the availability and distribution of inadequate supporting facilities and infrastructure at all levels of education according to national standards, as well as the urgent need to improve teachers' digital competence and literacy so they can adapt and teach innovatively in the era of the Industrial Revolution 4.0. This study uses a qualitative approach as the basic methodological framework because this approach is considered the most relevant for understanding in-depth the phenomenon of Information and Communication Technology (ICT) implementation in the context of learning in schools. The data collection technique used is interviews, because this technique is considered the most effective for gathering in-depth information regarding teachers' experiences, views, and practices in implementing ICT in learning. The results of the study indicate that the systematic application of ICT and supported by continuous training can improve teachers' understanding, technical skills, and positive attitudes towards digital technology. This transformation also has an impact on the creation of a collaborative and adaptive learning culture in the classroom. This article recommends the importance of institutional policies that support the digital ecosystem so that teachers' digital literacy continues to develop in line with the demands of the technological era. The contribution of this research is expected to provide a deeper understanding of the challenges and opportunities of digital classroom transformation at the junior high school level, while also producing strategic recommendations based on empirical evidence for policymakers and education practitioners so that digital transformation can improve the quality of learning sustainably.